An anti-perovskite catalyst, its preparation method and application

CN122937836APending Publication Date: 2026-10-20UNIV OF SCI & TECH BEIJING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611068089.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

这些均相催化剂的多电子氧化还原能力稳定且可逆,长期作为偶联反应的基准体系,但它们在催化剂分离回收、后处理成本及金属残留等方面存在明显不足

Benefits of technology

(1)晶体学限定的A(Ni、Co)、X(Zn、In)金属原子周期性排列,占位明确,活性结构清晰。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application provides an anti-perovskite catalyst, its preparation method, and its application, relating to the field of catalyst technology. The general chemical formula of the anti-perovskite catalyst is A3XY, where A is selected from nickel and / or cobalt, X is selected from zinc and / or indium, and Y is nitrogen. The preparation method of the anti-perovskite catalyst includes: mixing a metal salt of A, a metal salt of X, a precipitant, and water, followed by a hydrothermal reaction to obtain LDH precipitate; and sintering the LDH precipitate under an ammonia atmosphere to obtain the anti-perovskite catalyst. In the anti-perovskite catalyst provided by this application, Zn atoms are the main catalytic active sites for Michael addition reactions, and the reactivity of Zn is optimized by proximity to Ni atoms. This catalytic system is expected to serve as a novel, inexpensive metal catalyst for industrial organic coupling reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of catalyst technology, and in particular to an anti-perovskite catalyst, its preparation method, and its application. Background Technology

[0002] Cross-coupling (CC) in organocatalysis is a core strategy for constructing carbon skeletons, extending molecular frameworks, and introducing functional groups, playing an irreplaceable role in the synthesis of drug molecules, agrochemicals, and high-value-added fine chemicals. Its crucial position has been fully reflected in the 2010 and 2022 Nobel Prizes in Chemistry. Coupling reactions unfold around transition metal centers, achieving the construction of C-C bonds through a multi-electron cycle of "oxidative addition—transmetal / coordination exchange—reductive elimination."

[0003] Currently, coupling catalysts are classified into homogeneous and heterogeneous catalysts. The most common component is the noble metal palladium (Pd), followed by rhodium (Rh), ruthenium (Ru), iridium (Ir), platinum (Pt), and non-noble metals such as nickel (Ni) and copper (Cu). Homogeneous catalysts refer to catalysts and reactants in the same solution phase, with the active component dissolved in the solution for catalytic reaction. These homogeneous catalysts have stable and reversible multi-electron redox capabilities and have long served as the benchmark system for coupling reactions. However, they have significant shortcomings in terms of catalyst separation and recovery, post-processing costs, and metal residues. Therefore, heterogeneous catalysts have gradually become an important alternative system. Heterogeneous catalysts refer to catalysts in which the active metal is fixed on a support and does not dissolve in the solution during catalysis. They have advantages such as easy separation and recovery, structural stability, and lower industrial costs. Various heterogeneous catalysts developed in recent years, such as single-atom catalysts (SACs), diatomic catalysts (DACs), and co-atomic catalysts (GACs), further combine advantages such as high atom utilization, homogeneous coordination characteristics, dynamic synergistic activation of metals, and adaptability to complex coupling reactions.

[0004] Developing a novel anti-perovskite catalyst with high yield and low cost for industrial organic coupling reactions has become a research hotspot. Summary of the Invention

[0005] The purpose of this application is to provide an anti-perovskite catalyst, its preparation method, and its application, in order to solve the above-mentioned problems.

[0006] To achieve the above objectives, this application adopts the following technical solution: An anti-perovskite catalyst with the general chemical formula A3XY, wherein A is selected from nickel and / or cobalt, X is selected from zinc and / or indium, and Y is nitrogen.

[0007] Preferably, the anti-perovskite catalyst has a cubic crystal form with space group Pm-3m; in the crystal lattice, A occupies the face-centered position, Y occupies the body-centered position, and X occupies the vertex position, with A and Y forming a... <ni6n> 、 <co6n>Octahedral coordination structure.

[0008] Preferably, the chemical formula of the anti-perovskite catalyst is Ni3ZnN, (Ni 0.5 Co 0.5 )3ZnN and Co3ZnN.

[0009] This application also provides a method for preparing the aforementioned anti-perovskite catalyst, comprising: The metal salt of A, the metal salt of X, the precipitant, and water are mixed, and then a hydrothermal reaction is carried out to obtain LDH precipitate. The LDH precipitate was sintered under an ammonia atmosphere to obtain the anti-perovskite catalyst.

[0010] Preferably, the method for preparing the anti-perovskite catalyst satisfies one or more of the following conditions: (1) The metal salt of A includes nickel acetate and / or cobalt acetate; (2) The metal salt of X includes zinc acetate and / or indium acetate; (3) The precipitant includes hexamethylenetetramine; (4) The molar ratio of the precipitant to the metal salt of A is 4.5-5.0:1.5-2.4.

[0011] Preferably, the method for preparing the anti-perovskite catalyst satisfies one or more of the following conditions: (1) The temperature of the hydrothermal reaction is 115-125℃ and the time is 11.5-12h; (2) The LDH precipitate is washed and dried with deionized water and ethanol respectively before sintering; (3) The flow rate of the ammonia gas is 90-100 ml / min; (4) The sintering temperature is 500-510℃ and the time is 6-6.5h.

[0012] This application also provides an application of the aforementioned anti-perovskite catalyst for coupling addition reactions.

[0013] Preferably, the coupling addition reaction includes indole and ( E The reaction using 2-nitrovinyl)benzene as a raw material.

[0014] Preferably, the indole and the ( E Reactions using 2-nitrovinyl)benzene as a starting material include: The indole, the ( E The indole addition product is obtained by mixing (2-nitrovinyl)benzene, the anti-perovskite catalyst, a base, and an organic solvent, stirring the reaction mixture, and then performing post-treatment.

[0015] Preferably, the application of the anti-perovskite catalyst satisfies one or more of the following conditions: (1) The base includes triethylamine; (2) The organic solvent includes 1,4-dioxane; (3) As stated in ( E The molar amount of 2-nitrovinyl)benzene is used as the basis for measurement, the amount of indole is 1.1-2.0 equivalents, and the amount of base is 1.1-2.0 equivalents; (4) The amount of the anti-perovskite catalyst is as described above. E The molar amount of 2-10% of 2-nitrovinyl)benzene; (5) The organic solvent and the ( E The molar ratio of 1.0-1.1 mL to 0.1 mmol of 2-nitrovinyl)benzene is 1.0-1.1 mL. (6) The temperature of the stirring reaction is 115℃ and the time is 23.5-24.5h.

[0016] Compared with the prior art, the beneficial effects of this application include: The anti-perovskite catalyst provided in this application has the following advantages: (1) Crystallographically defined periodic arrangement of A (Ni, Co) and X (Zn, In) metal atoms with clear site occupancy and distinct active structure.

[0017] The outermost exposed crystal plane of the catalyst particle is the (100) crystal plane. On the surface crystal plane (100), the crystallographic positions of A (Ni, Co) and X (Zn, In) metal atoms are fixed and arranged in an ordered rather than random manner. The local stoichiometry of each position strictly follows a 1:1 ratio, forming an ordered A (Ni, Co) and X (Zn, In) metal network. On the internal (200) crystal plane, A (Ni, Co) metal and N (nitrogen) form an ordered AN network. The coordination structure of A (Ni, Co) on each crystal plane has a clear crystallographic definition. This fixed, ordered, and proportionally proportioned Ni-Zn periodic arrangement is the key to achieving high selectivity and high yield.

[0018] Existing noble metal (Pd, Rh, Ru, Ir, etc.) nanoparticle catalysts have various active sites on their surfaces (such as edge sites, step sites, defect sites, and apex sites), and surface atoms easily recombine into clusters during the reaction, making it difficult to determine the true active sites in experiments, and resulting in low product yields. Furthermore, the use of noble metals makes the catalysts expensive.

[0019] Existing disordered alloys formed by precious and inexpensive metals, such as PdNi palladium-nickel alloy catalysts, exhibit Pd and Ni metal atoms randomly occupying the same lattice sites, and the Pd:Ni stoichiometry at different positions randomly deviates from the overall average stoichiometry. This means that the active site structure can only be described statistically, while the true local active structure remains unclear. These characteristics reduce reaction selectivity and yield, and hinder understanding the mechanism and optimizing catalyst design. (2) Similar metal atoms are spatially isolated, while dissimilar metal atoms are coupled in close proximity.

[0020] Taking Ni and Zn as examples, the Ni and Zn atoms in the catalyst are isolated from each other. The atomic spacing between Ni and Ni, and between Zn and Zn, is approximately 3.8 Å, which exceeds the bonding range. This results in isolated Ni and Zn sites, i.e., single-atom dispersed arrays of Ni and Zn atoms. This helps suppress the aggregation and clustering tendency of similar metal atoms in the reaction, avoiding interference from multi-atom clusters of active centers common in metal catalysts. In contrast, on the surface of existing catalysts, Pd and Ni atoms tend to aggregate during the reaction, forming clusters that affect reaction activity and reduce reaction yield.

[0021] Ni and Zn atoms are coupled in close proximity, with a spacing of approximately 2.7 Å between them, which falls within the bond length range suitable for bimetallic coupling. This creates a periodic Ni-Zn coupling structure and a stable metal-metal electronic synergistic channel, forming a synergistic catalytic mechanism. In contrast, current alloy catalysts (such as PdNi alloys) have randomly and randomly occupied Pd and Ni atoms, lacking a periodic coupling structure, resulting in limited synergistic regulation and catalytic selectivity.

[0022] Co and In have similar situations.

[0023] (3) Lattice constraints enhance the stability of atomic sites.

[0024] On the one hand, after metal atoms are embedded into the anti-perovskite lattice, they can form stable coordination through metal bonds and metal-N bonds, making it difficult for metal atoms to desorb or migrate and recombine into clusters. In contrast, existing single-atom catalysts, such as Cu-C3N4 catalysts and Ni / C catalysts, have metal atoms that easily detach from the carbon matrix, leading to rapid performance degradation.

[0025] On the other hand, anti-perovskites possess a long-range ordered lattice structure, exhibiting better thermodynamic structural stability. In contrast, existing alloy catalysts, due to their disordered metal arrangement, suffer from inferior thermodynamic stability compared to the ordered lattice of anti-perovskites. Therefore, the ordered structure of anti-perovskites is more conducive to enhancing atomic site stability under reaction conditions.

[0026] The anti-perovskite catalyst provided in this application is a nanoparticle powder with a long-range ordered anti-perovskite lattice in its crystal structure. Experiments revealed that Zn atoms are the main catalytically active sites for the Michael addition reaction, and the reactivity of Zn is optimized by proximity to Ni atoms. Zn couples β-nitrostyrene with indole, attaching the C3 position of the indole to a 2-nitro-1-phenylethyl fragment during the reaction, resulting in a 70% yield of 3-(2-nitro-1-phenylethyl)-1H-indole. This catalytic system shows promise as a novel, inexpensive metal catalyst for industrial organic coupling reactions.

[0027] The preparation method used in this application is hydrothermal synthesis and high-temperature sintering. The raw materials required for the synthesis are all inexpensive reagents, and the overall synthesis route is low-cost and suitable for industrial scale-up.

[0028] The anti-perovskite catalyst provided in this application can be widely used in organic coupling reactions. Attached Figure Description

[0029] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.

[0030] Figure 1 The XRD data of the catalyst Ni3ZnN obtained in Example 1 are the Rietveld refined pattern. Figure 2 The catalyst (Ni) obtained in Example 2 0.5 Co 0.5 XRD data of 3ZnN and Rietveld refined spectra; Figure 3 The XRD data of the catalyst Co3ZnN obtained in Example 2 are the Rietveld refined pattern. Figure 4 Ni3Zn 0.5 In 0.5 XRD refinement fitting plot of N; Figure 5 The refined XRD pattern of Ni3InN; Figure 6 The XRD pattern of Ni nanoparticles is a refined fit. Figure 7 The XRD pattern of ZnO particles is a refined fit. Figure 8 The product of the reaction catalyzed by Ni3ZnN catalyst 1 H NMR spectrum (400 MHz, CDCl3); Figure 9 The mass spectra of the catalytic products of the Ni3ZnN catalyst are shown. Detailed Implementation

[0031] To better illustrate the technical solution provided in this application, the technical solution will be described in its entirety before the embodiments, as follows: An anti-perovskite catalyst with the general chemical formula A3XY, wherein A is selected from nickel and / or cobalt, X is selected from zinc and / or indium, and Y is nitrogen.

[0032] In an optional embodiment, the anti-perovskite catalyst has a cubic crystal form with space group Pm-3m; in the crystal lattice, A occupies the face-centered position, Y occupies the body-centered position, and X occupies the vertex position, with A and Y forming a... <ni6n> 、 <co6n>Octahedral coordination structure.

[0033] In an optional embodiment, the anti-perovskite catalyst has the chemical formula Ni3ZnN, (Ni 0.5 Co 0.5 )3ZnN and Co3ZnN.

[0034] This application also provides a method for preparing the aforementioned anti-perovskite catalyst, comprising: The metal salt of A, the metal salt of X, the precipitant, and water are mixed, and then a hydrothermal reaction is carried out to obtain LDH precipitate. The LDH precipitate was sintered under an ammonia atmosphere to obtain the anti-perovskite catalyst.

[0035] In an optional embodiment, the method for preparing the anti-perovskite catalyst satisfies one or more of the following conditions: (1) The metal salt of A includes nickel acetate and / or cobalt acetate; (2) The metal salt of X includes zinc acetate and / or indium acetate; (3) The precipitant includes hexamethylenetetramine; (4) The molar ratio of the precipitant to the metal salt of A is 4.5-5.0:1.5-2.4 (which can be any value between 4.5:1.5, 4.8:2, 5.0:2.4 or 4.5-5.0:1.5-2.4).

[0036] In an optional embodiment, the method for preparing the anti-perovskite catalyst satisfies one or more of the following conditions: (1) The temperature of the hydrothermal reaction is 115-125℃ (which can be any value between 115℃, 120℃, 125℃) and the time is 11.5-12h (which can be any value between 11.5h, 11.8h, 12h or 11.5-12h). (2) The LDH precipitate is washed and dried with deionized water and ethanol respectively before sintering; (3) The flow rate of the ammonia gas is 90-100 ml / min (which can be any value between 90 ml / min, 95 ml / min, 100 ml / min or 90-100 ml / min). (4) The sintering temperature is 500-510℃ (which can be any value between 500℃, 505℃, 510℃ or 500-510℃), and the time is 6-6.5h (which can be any value between 6h, 6.2h, 6.5h or 6-6.5h).

[0037] This application also provides an application of the aforementioned anti-perovskite catalyst for coupling addition reactions.

[0038] In an optional embodiment, the coupling addition reaction includes indole and ( E The reaction using 2-nitrovinyl)benzene as a raw material.

[0039] In an optional implementation, the indole and the ( E Reactions using 2-nitrovinyl)benzene as a starting material include: The indole, the ( E The indole addition product is obtained by mixing (2-nitrovinyl)benzene, the anti-perovskite catalyst, a base, and an organic solvent, stirring the reaction mixture, and then performing post-treatment.

[0040] In an optional embodiment, the application of the anti-perovskite catalyst satisfies one or more of the following conditions: (1) The base includes triethylamine; (2) The organic solvent includes 1,4-dioxane; (3) As stated in ( E The amount of 2-nitrovinyl)benzene is used as the basis for measurement, the amount of indole is 1.1-2.0 equivalents (which can be any value between 1.1 equivalents, 1.5 equivalents, 2.0 equivalents, or 1.1-2.0 equivalents), and the amount of base is 1.1-2.0 equivalents (which can be any value between 1.1 equivalents, 1.5 equivalents, 2.0 equivalents, or 1.1-2.0 equivalents). (4) The amount of the anti-perovskite catalyst is as described above. E The molar amount of 2-10% of (2-nitrovinyl)benzene (can be any value between 0 and 10); (5) The organic solvent and the ( E The molar ratio of 1-(2-nitrovinyl)benzene is 1.0-1.1 mL : 0.1 mmol (which can be any value between 1.0 mL : 0.1 mmol, 1.05 mL : 0.1 mmol, or 1.0-1.1 mL : 0.1 mmol). (6) The temperature of the stirring reaction is 115-125℃ (which can be any value between 115℃, 120℃, 125℃) and the time is 23.5-24.5h (which can be any value between 23.5h, 24h, 24.5h or 23.5-24.5h).

[0041] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.

[0042] Example 1 This embodiment provides an anti-perovskite catalyst Ni3ZnN, the preparation method of which is as follows: 2.4 mmol of nickel acetate and 0.8 mmol of zinc acetate were dissolved together in 50 mL of deionized water, ensuring a Ni:Zn molar ratio of 3:1. After complete dissolution, 5 mmol of hexamethylenetetramine (HMT) was added, and the mixture was stirred vigorously for 2 hours until homogeneous. The liquid was transferred to a hydrothermal reactor and reacted in an oven at 120 °C for 12 hours to generate LDH precipitate. After natural cooling, the precipitate was removed, centrifuged, and washed once each with deionized water and ethanol. The LDH was dried, transferred to a tube furnace, and sintered at 500 °C for 6 hours under an ammonia atmosphere (flow rate 100 mL / min). After natural cooling to room temperature, argon gas was introduced to remove the ammonia, and the final product, Ni3ZnN, was collected and stored in a glove box.

[0043] Example 2 This embodiment provides an anti-perovskite catalyst (Ni 0.5 Co 0.5 3ZnN, its preparation method is as follows: 1.2 mmol of nickel acetate, 1.2 mmol of cobalt acetate, and 0.8 mmol of zinc acetate were dissolved together in 48 mL of deionized water. The total amount of nickel acetate and cobalt acetate was ensured to be 2.4 mmol, and the molar ratio of their total amount to Zn was 3:1. After complete dissolution, 4.8 mmol of hexamethylenetetramine (HMT) was added, and the mixture was stirred vigorously for 1.8 hours until homogeneous. The liquid was transferred to a hydrothermal reactor and reacted in an oven at 120 °C for 11.8 hours to generate LDH precipitate. After natural cooling, the precipitate was removed, centrifuged, and washed once each with deionized water and ethanol. The LDH was dried, transferred to a tube furnace, and sintered at 500 °C for 6 hours under an ammonia atmosphere (flow rate 95 mL / min). After natural cooling to room temperature, argon gas was introduced to remove the ammonia, and then the final product (Ni) was collected. 0.5 Co 0.5 3ZnN, stored in a glove box.

[0044] Example 3 This embodiment provides an anti-perovskite catalyst Co3ZnN, the preparation method of which is as follows: 1.5 mmol of cobalt acetate and 0.5 mmol of zinc acetate were dissolved together in 45 mL of deionized water. After complete dissolution, 4.5 mmol of hexamethylenetetramine (HMT) was added, and the mixture was stirred vigorously for 1.5 hours until it was uniformly dissolved and dispersed. The liquid was transferred to a hydrothermal reactor and reacted in an oven at 120 °C for 11.5 hours to generate LDH precipitate. After natural cooling, the precipitate was removed, centrifuged, and washed once each with deionized water and ethanol. The LDH was dried, transferred to a tube furnace, and sintered at 510 °C for 6.5 hours under an ammonia atmosphere (flow rate 90 mL / min). After natural cooling to room temperature, argon gas was purged to remove the ammonia, and the final product, Co3ZnN, was collected and stored in a glove box.

[0045] Example 4 This embodiment provides an anti-perovskite catalyst Ni3InN, the preparation method of which is as follows: 2.4 mmol of nickel acetate and 0.8 mmol of indium acetate were dissolved together in 50 mL of deionized water, ensuring a Ni to In molar ratio of 3:1. After complete dissolution, 5 mmol of hexamethylenetetramine (HMT) was added, and the mixture was stirred vigorously for 2 hours until it was uniformly dissolved and dispersed. The liquid was transferred to a hydrothermal reactor and reacted in an oven at 120 °C for 12 hours to generate LDH precipitate. After natural cooling, the precipitate was removed, centrifuged, and washed once each with deionized water and ethanol. The LDH was dried, transferred to a tube furnace, and sintered at 500 °C for 6 hours under an ammonia atmosphere (flow rate 100 mL / min). After natural cooling to room temperature, argon gas was purged to remove the ammonia, and the final product, Ni3InN, was collected and stored in a glove box.

[0046] Example 5 This embodiment provides an anti-perovskite catalyst Ni3Zn 0.5 In 0.5 N is prepared as follows: 2.4 mmol of nickel acetate, 0.4 mmol of zinc acetate, and 0.4 mmol of indium acetate were dissolved together in 50 mL of deionized water. After complete dissolution, 5 mmol of hexamethylenetetramine (HMT) was added, and the mixture was stirred vigorously for 2 hours until it was uniformly dissolved and dispersed. The liquid was transferred to a hydrothermal reactor and reacted in an oven at 120 °C for 12 hours to generate LDH precipitate. After natural cooling, the precipitate was removed, centrifuged, and washed once each with deionized water and ethanol. The LDH was dried, transferred to a tube furnace, and sintered at 500 °C for 6 hours under an ammonia atmosphere (flow rate 100 mL / min). After natural cooling to room temperature, argon gas was introduced to wash away the ammonia, and then the final product Ni3Zn was collected. 0.5 In 0.5 N, store in the glove box.

[0047] Comparative Example 1 Nickel nanoparticles (Ni).

[0048] 2.4 mmol of nickel acetate was dissolved in 50 mL of deionized water. After complete dissolution, 5 mmol of hexamethylenetetramine (HMT) was added, and the mixture was stirred vigorously for 2 hours until it was uniformly dissolved and dispersed. The liquid was transferred to a hydrothermal reactor and reacted in an oven at 120 °C for 12 hours to generate LDH precipitate. After natural cooling, the precipitate was removed, centrifuged, and washed once each with deionized water and ethanol. The LDH was dried, transferred to a tube furnace, and sintered at 500 °C for 6 hours under an ammonia atmosphere (flow rate 100 mL / min). After natural cooling to room temperature, argon gas was purged to remove the ammonia, and the final product was then stored in a glove box.

[0049] Comparative Example 2 Zinc oxide (ZnO).

[0050] Dissolve 2.4 mmol of zinc acetate in 50 mL of deionized water. After complete dissolution, add 5 mmol of hexamethylenetetramine (HMT) and stir vigorously for 2 hours until dissolved and evenly dispersed. Transfer the liquid to a hydrothermal reactor and react in an oven at 120 °C for 12 hours to generate LDH precipitate. After natural cooling, remove the precipitate, separate it by centrifugation, and wash it once each with deionized water and ethanol. Dry the LDH, transfer it to a tube furnace, and sinter it at 500 °C for 6 hours under an ammonia atmosphere (flow rate 100 mL / min). After natural cooling to room temperature, purge the ammonia with argon gas, and store the final product in a glove box.

[0051] 1. XRD phase analysis Figure 1 The image shows the Rietveld refined XRD pattern of the Ni3ZnN catalyst obtained in Example 1. Blue circles represent measured data, red lines represent fitted spectra based on the crystal structure, and gray lines represent the difference between measured and fitted data. The small blue vertical line at the bottom indicates the diffraction index peak positions of this structure. First, through phase search and combining the diffraction peak positions from the standard crystal structure cards in the International Crystal Database (ICSD), it was found that all diffraction peaks could be identified by anti-perovskite Ni3ZnN, and the phase purity was high, with no impurities present. Therefore, the phase was confirmed to be anti-perovskite Ni3ZnN.

[0052] The Ni3ZnN crystal structure model (containing atomic coordinates and other parameters) from the International Crystal Database (ICSD) was then used as the initial model and substituted into the XRD data for fine-tuning and fitting. Ultimately, all diffraction peaks were well fitted, with a fitting residual factor Rwp of only 1.5% (below 5% is considered a good fit). This determined the actual anti-perovskite structure of the obtained phase. The structure is a cubic lattice with space group Pm-3m and cell parameter a = 3.7650 Å. Ni occupies the face-centered position at coordinates (0.5, 0.5, 0). Zn occupies the vertex position at coordinates (0, 0, 0). N occupies the body-centered position at coordinates (0.5, 0.5, 0.5).

[0053] Figure 2 The catalyst (Ni) obtained in Example 2 0.5 Co 0.5 XRD data of 3ZnN, Rietveld refined spectrum. Blue circles represent measured data, red represent fitted spectra based on crystal structure, and gray represent the difference between measured and fitted spectra. This sample contains 2.49% ZnO impurities and 97.51% NiO. 0.5 Co 0.5 )3ZnN. We use black lines to indicate the contribution of ZnO to the diffraction pattern. The small blue vertical line at the bottom represents (Ni). 0.5 Co 0.5 The diffraction index of 3ZnN is shown. The small black vertical lines represent the diffraction index of ZnO. Similarly, phase searching based on the ICSD database confirms the presence of anti-perovskite (Ni) in the XRD. 0.5 Co 0.5 )3ZnN and a very small amount of ZnO impurities. Substituting (Ni) 0.5 Co 0.5 The initial structural models of 3ZnN and ZnO were refined and fitted, ultimately achieving a good fit for all diffraction peaks. The fitting residual factor Rwp was only 1.7%. (Ni...) 0.5 Co 0.5 The ZnN content was 97.51%, and the ZnO content was 2.49%. The actual anti-perovskite structure obtained was a cubic lattice with space group Pm-3m and cell parameter a = 3.7639 Å. Ni and Co were in equal proportions and randomly occupied the face-centered positions, with coordinates (0.5, 0.5, 0). Zn occupied the vertex positions with coordinates (0, 0, 0). N occupied the body-centered position with coordinates (0.5, 0.5, 0.5).

[0054] Figure 3 The image shows the Rietveld refined XRD pattern of the Co3ZnN catalyst obtained in Example 3. Blue circles represent measured data, red circles represent fitted spectra based on the crystal structure, and gray circles represent the difference between measured and fitted data. This sample contains 2.39% ZnO impurities and 97.61% Co3ZnN. The contribution of ZnO to the diffraction pattern is indicated by a black line. The small blue vertical line at the bottom represents the diffraction index of Co3ZnN. The small black vertical line represents the diffraction index of ZnO. Phase searching based on the ICSD database confirmed the presence of anti-perovskite Co3ZnN and a small amount of ZnO impurities in the XRD. Substituting the initial structural models of Co3ZnN and ZnO for refined fitting resulted in a good fit of all diffraction peaks. The fitting residual factor Rwp was only 1.4%. The Co3ZnN content was 97.61%, and the ZnO content was 2.39%. The actual anti-perovskite structure obtained is a cubic lattice with space group Pm-3m and cell parameter a = 3.7575 Å. Co occupies the face-centered positions with coordinates (0.5, 0.5, 0). Zn occupies the vertex positions with coordinates (0, 0, 0). N occupies the body-centered positions with coordinates (0.5, 0.5, 0.5).

[0055] Figures 4 to 7 Ni3Zn in sequence 0.5 In 0.5 XRD patterns of N, Ni3InN, Ni nanoparticles and ZnO particles. Figure 4 Ni3Zn 0.5 In 0.5 The refined XRD pattern of Ni3Zn is shown; blue circles represent measured data, red lines represent fitted spectra based on the crystal structure, and gray lines represent the difference between measured and fitted data. The small blue vertical line at the bottom represents Ni3Zn. 0.5 In 0.5 Diffraction index of N. Figure 5 The image shows the refined XRD pattern of Ni3InN; blue circles represent measured data, red lines represent fitted spectra based on the crystal structure, and gray lines represent the difference between measured and fitted data. The small blue vertical line at the bottom represents the diffraction index of Ni3InN. Figure 6 The image shows the refined XRD pattern of Ni nanoparticles; the blue circles represent measured data, the red lines represent fitted spectra based on the crystal structure, and the gray lines represent the difference between the measured and fitted spectra. The small blue vertical line at the bottom represents its diffraction index. Figure 7 The XRD patterns of ZnO particles are shown in the refined fitted XRD patterns. Blue circles represent measured data, red lines represent fitted spectra based on the crystal structure, and gray lines represent the difference between measured and fitted data. The small blue vertical line at the bottom represents their diffraction index. All four control samples are pure phases, and no diffraction peaks of impurities were observed in their XRD patterns. All four patterns can be well fitted by their structural models, fully demonstrating the accuracy of the phase identification. Figure 4 In the middle, Ni3Zn 0.5 In 0.5 The residual factor Rwp for the N spectrum fitting is 2.1%. Its structure is a cubic lattice with space group Pm-3m and cell parameter a = 3.8171 Å. Ni occupies the face-centered positions, with coordinates (0.5, 0.5, 0). Zn and In are randomly mixed in equal proportions at the vertex positions, with coordinates (0, 0, 0). N occupies the body-centered position, with coordinates (0.5, 0.5, 0.5). Figure 5 In the model, the residual factor Rwp for fitting the Ni3InN spectrum is 1.7%. Its structure is a cubic lattice with space group Pm-3m and cell parameter a = 3.8638 Å. Ni occupies the face-centered positions with coordinates (0.5, 0.5, 0). In occupies the vertex positions with coordinates (0, 0, 0). N occupies the body-centered positions with coordinates (0.5, 0.5, 0.5). Figure 6 In the XRD pattern fitting residual factor Rwp of Ni metal nanoparticles, the value is 1.9%. It has a face-centered cubic structure with cell parameter a = 3.5238 Å and Ni coordinates (0, 0, 0). Figure 7 In the XRD pattern fitting, the residual factor Rwp of the ZnO particles is 2.2%. It has a hexagonal structure, P63mc, a=b=3.2489 Å, c=5.2054 Å. The Zn atom coordinates are (1 / 3, 2 / 3, 0), and the O atom coordinates are (1 / 3, 2 / 3, 0.382).

[0056] 2. Analysis of Organic Catalytic Performance The catalytic performance was studied using standard organic catalysis methods. A coupling addition reaction was carried out using indole and (E)-(2-nitrovinyl)benzene as reactants. In an inert atmosphere glove box, the catalyst, (E)-(2-nitrovinyl)benzene, indole, triethylamine, and organic solvent were added sequentially to a dry, pressure-resistant reaction tube. The amounts of catalyst and indole were 2–10% molar relative to (E)-(2-nitrovinyl)benzene, 0.1 mmol (as a primary standard), 1.1–2.0 equivalents of indole, 1.1–2.0 equivalents of triethylamine, and 1.0–1.1 mL of 1,4-dioxane as the organic solvent. After the addition was complete, the reaction tube was sealed and removed from the glove box, and the reaction was stirred at 120 °C for 24 h. After the reaction is complete, the reaction system is cooled to room temperature, the solid catalyst is removed by an appropriate method, and the resulting reaction solution is concentrated and purified to obtain the corresponding indole addition product. Alternatively, after the reaction is complete, the reaction system is cooled to room temperature, the catalyst is removed by solid-liquid separation, and the resulting liquid phase is treated by concentration, extraction, column chromatography, recrystallization, or other conventional separation and purification methods to obtain the target product.

[0057] Ni3ZnN: The amount of Ni3ZnN used was 5.0% molar relative to (E)-(2-nitrovinyl)benzene, the amount of (E)-(2-nitrovinyl)benzene was 0.1 mmol, the amount of indole was 1.5 equivalents, the amount of triethylamine was 1.5 equivalents, and the organic solvent was 1,4-dioxane, with a volume of 1.0 mL. The reaction was stirred at 120 °C for 24 h. Subsequent treatments were then carried out according to the above method.

[0058] (Ni) 0.5 Co 0.5 The following organic solvents were used: 3ZnN (5.2% molar amount relative to (E)-(2-nitrovinyl)benzene), (E)-(2-nitrovinyl)benzene (0.1 mmol), indole (1.6 equivalents), triethylamine (1.6 equivalents), and 1,4-dioxane (1.1 mL). The reaction was carried out with stirring at 120 °C for 24 h. Subsequent treatments were then performed as described above.

[0059] The amount of Co3ZnN used was 5.1 mol% relative to (E)-(2-nitrovinyl)benzene, with (E)-(2-nitrovinyl)benzene accounting for 0.1 mmol, indole accounting for 1.7 equivalents, triethylamine accounting for 1.7 equivalents, and 1,4-dioxane as the organic solvent accounting for 1.0 mL. The reaction was stirred at 120 °C for 24 h. Subsequent treatments were then carried out as described above.

[0060] Ni3InN, Ni3Zn 0.5 In 0.5 The experimental conditions for N, as well as the nano-metal particles Ni and zinc oxide ZnO, were consistent with those for Ni3ZnN. The amounts used were 5.0 mol% relative to (E)-(2-nitrobenzene)benzene, with (E)-(2-nitrobenzene)benzene at 0.1 mmol, indole at 1.5 equivalents, triethylamine at 1.5 equivalents, and 1,4-dioxane as the organic solvent at 1.0 mL. The reaction was carried out with stirring at 120 °C for 24 h. Subsequent treatments were then performed as described above.

[0061] The product spectral data of the catalyst Ni3ZnN are presented here. After separation, purification, and extraction, the obtained product is a yellow solid powder. Figure 8 The 1H NMR spectrum of the product is shown below. The analysis results are as follows: 1 ¹H NMR (400MHz, deuterated chloroform CDCl₃ as solvent) δ 8.15 (s, 1H), 7.48 (d, J = 7.1 Hz, 1H), 7.41–7.33 (m, 5H), 7.31–7.27 (m, 1H), 7.23 (t, J = 7.1 Hz, 1H), 7.11 (t, J = 7.5 Hz, 1H), 7.05 (d, J = 1.6 Hz, 1H), 5.25–5.19 (m, 1H), 5.10 (dd, J = 12.5, 7.7 Hz, 1H), 4.97 (dd, J = 12.5, 8.4 Hz, 1H) ppm. Based on standard cards from the organic molecular NMR database, the product was identified as 3-(2-nitro-1-phenylethyl)-1H-indole, with the following molecular structure: Figure 8 As shown in the upper left corner.

[0062] The NMR spectra of the products from other catalysts and control group samples were the same, and the products were also identical.

[0063] Based on the above analysis, the catalytic reaction formula is determined to be: ; In the formula, 1 is β-nitrostyrene, 2 is indole, and 3 is the product 3-(2-nitro-1-phenylethyl)-1H-indole.

[0064] The reaction process involves the attachment of the C3 position of indole to a 2-nitro-1-phenylethyl fragment under the action of a catalyst, forming the final product. Figure 9 Mass spectrometry analysis of the catalytic products of the Ni3ZnN catalyst is presented. The mass-to-charge ratios of the main signals are indicated in the figure. The signal with a mass-to-charge ratio of 266.0 corresponds to the characteristic signal of this product. The other signals are mostly from the reactants.

[0065] The yield of the product can be obtained from the integrated area of ​​the mass spectrometry signal. The product yield of the Ni3ZnN catalyst is 70%.

[0066] The yields of other catalysts are shown in Table 1.

[0067] Table 1 Catalytic yields of 3-(2-nitro-1-phenylethyl)-1H-indole for each catalyst and control sample

[0068] Replacing Zn with In, i.e., Ni3(Zn) 0.5 In 0.5 Replacing Zn entirely with In (Ni3InN) reduces the yield to 15%. Completely replacing Zn with In (Ni3InN) results in a yield of only 5%. This demonstrates the crucial role of Zn. Furthermore, partially replacing Ni with Co (Ni3InN) further reduces the yield to 15%. 0.5 Co 0.5 Replacing Ni entirely with Co (Co3ZnN) reduces the yield to 49%. Replacing all Ni with Co further reduces the yield to 42%, indicating that Ni has a supporting role. Furthermore, the yield of Ni nanoparticles is only 3%, while the yield of ZnO is 38%, clearly demonstrating that Ni itself has very low activity. Zn plays a major role in catalysis, and Ni's role is to optimize and enhance the activity of Zn.

[0069] In summary, the anti-perovskite Ni3ZnN in this application exhibits the best catalytic yield, while the (Ni) in this application... 0.5 Co 0.5 The catalytic yields of ZnN and Co3ZnN were also higher than those of the comparative samples, especially higher than those of ZnO itself. Furthermore, all three yields were higher than those of the previously reported existing metal salt catalyst NiCl2 (catalytic yield 20%). This fully demonstrates the advantages of the anti-perovskite catalyst provided in this application.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application. < / ni6n> < / ni6n>

Claims

1. An anti-perovskite catalyst, characterized in that, Its general chemical formula is A3XY, where A is selected from nickel and / or cobalt, X is selected from zinc and / or indium, and Y is nitrogen.

2. The anti-perovskite catalyst according to claim 1, characterized in that, The anti-perovskite catalyst has a cubic crystal form with space group Pm-3m; in the crystal lattice, A occupies the face-centered position, Y occupies the body-centered position, and X occupies the vertex position. A and Y form a... <ni6n> 、 <co6n> Octahedral coordination structure.< / co6n> < / ni6n> 3. The anti-perovskite catalyst according to claim 1 or 2, characterized in that, The chemical formula of the anti-perovskite catalyst is Ni3ZnN, (Ni 0.5 Co 0.5 )3ZnN and Co3ZnN.

4. A method for preparing an anti-perovskite catalyst according to any one of claims 1-3, characterized in that, include: The metal salt of A, the metal salt of X, the precipitant, and water are mixed, and then a hydrothermal reaction is carried out to obtain LDH precipitate. The LDH precipitate was sintered under an ammonia atmosphere to obtain the anti-perovskite catalyst.

5. The method for preparing the anti-perovskite catalyst according to claim 4, characterized in that, One or more of the following conditions must be met: (1) The metal salt of A includes nickel acetate and / or cobalt acetate; (2) The metal salt of X includes zinc acetate and / or indium acetate; (3) The precipitant includes hexamethylenetetramine; (4) The molar ratio of the precipitant to the metal salt of A is 4.5-5.0:1.5-2.

4.

6. The method for preparing the anti-perovskite catalyst according to claim 4 or 5, characterized in that, One or more of the following conditions must be met: (1) The temperature of the hydrothermal reaction is 115-125℃ and the time is 11.5-12h; (2) The LDH precipitate is washed and dried with deionized water and ethanol respectively before sintering; (3) The flow rate of the ammonia gas is 90-100 ml / min; (4) The sintering temperature is 500-510℃ and the time is 6-6.5h.

7. The application of the anti-perovskite catalyst according to any one of claims 1-3, characterized in that, Used for coupling addition reactions.

8. The application of the anti-perovskite catalyst according to claim 7, characterized in that, The coupling addition reaction includes indole and ( E The reaction using 2-nitrovinyl)benzene as a raw material.

9. The application of the anti-perovskite catalyst according to claim 8, characterized in that, The indole and the ( E Reactions using 2-nitrovinyl)benzene as a starting material include: The indole, the ( E The indole addition product is obtained by mixing (2-nitrovinyl)benzene, the anti-perovskite catalyst, a base, and an organic solvent, stirring the reaction mixture, and then performing post-treatment.

10. The application of the anti-perovskite catalyst according to claim 9, characterized in that, One or more of the following conditions must be met: (1) The base includes triethylamine; (2) The organic solvent includes 1,4-dioxane; (3) As stated in ( E The molar amount of 2-nitrovinyl)benzene is used as the basis for measurement, the amount of indole is 1.1-2.0 equivalents, and the amount of base is 1.1-2.0 equivalents; (4) The amount of the anti-perovskite catalyst is as described above. E The molar amount of 2-10% of 2-nitrovinyl)benzene; (5) The organic solvent and the ( E The molar ratio of 1.0-1.1 mL to 0.1 mmol of 2-nitrovinyl)benzene is 1.0-1.1 mL. (6) The temperature of the stirring reaction is 115-125℃ and the time is 23.5-24.5h.